GREEN STRATEGY PERUSAHAAN PLASTIK DALAM MENGHADAPI TANTANGAN LINGKUNGAN DAN PEMERINTAH - Theresia Gunawan; Michael Alexander Ferdhian (Business Administration Department - Universitas Katolik Parahyangan, 2020)
The plastic industry is one of the growing industries because the plastic packaging industry plays an important role in the supply chain for strategic sectors such as food and beverages, pharmaceuticals, cosmetics, and electronics. However, the plastics industry also faces many challenges from government policies due to its regulation to reduce the use of plastic packaging. Indonesia is acknowledged as the second-largest contributor to plastic waste after China. This has led to big cities in Indonesia initiate policies to reduce and to ban plastic use. This certainly can be a problem for plastic companies. Therefore, the company should have a good strategy in dealing with that policy. In this study, the authors try to analyze strategies that are appropriate for PT DHI to be able to survive facing policies that put pressure on PT DHI. By conducting interviews, observations, and analyzing various internal and external factors and SWOT matrix analysis shows that PT. DHI besides running the existing products, PT. DHI has to start developing environmentally friendly plastic bag products and take the opportunity that there are 15% - 46% potential customers that will choose green products